The anthropological construction of Czech identity: academic and popular discourses of identity in 20th century Bohemia - Vimont, M; Michael Timothy Vimont (2015)
Through close textual analysis of 20th century Czech anthropological texts from the Revivalist and Socialist periods and contemporary social research conducted after the Velvet Revolution, I demonstrate certain prominent discourses of identity developed in early Bohemian anthropology and their continuities in present day popular discourses. In each period, identity is deeply intertwined with teleological theories of history with Czech populations at the apex of cultural evolutionary development. In the Revivalist period this apex was believed to be the democratic nation state, transitioning to a Marxist nation state in the Socialist period, and in the contemporary period is conceived of as a neoliberal nation state. A major function of anthropology in the Revivalist and Socialist periods was to legitimate either period’s respective teleological theory and Czech possession of relevant values as 'objective' and 'natural' fact, a general mode of discourse which continued in the contemporary period in numerous editorials in the 1990s on the advantages of capitalism. The contemporary manifestation has particularly noteworthy consequences for the Roma minority, which I argue has provided Czech discourses with an ethnic category 'anti-thetical' to their own identity, providing a 'repository' for negative Czech self-stereotypes emerging from collaboration in the Socialist period.